Does drinking coffee reduce the risk of kidney stone formation? - Elwira Servaas; Olga Grelewicz; Adam Juśkiewicz; Mateusz Haber; Adrianna Czachor; Alicja Kotula; Paula Kula; Natalia Kucy; Robert Siemiątkowski (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Kidney stones, a prevalent urological issue affecting 2% to 15% of the global population, result from complex physicochemical processes in urine. Untreated stones can lead to severe complications like ureter blockage and kidney damage. Diet plays a crucial role in stone formation, with historical negative views on coffee consumption. However, new research shows potential benefits of coffee. The purpose of this review was to analyze the association between coffee consumption and the risk of developing kidney stones. State of knowledge: Kidney stones develop as solid masses in the kidney's collecting system and can consist of various substances like calcium oxalate, calcium phosphate, uric acid, and cystine. Understanding the formation of kidney stones involves analyzing the role of crystal retention. Coffee consumption has shown potential benefits in reducing the risk of kidney stones by influencing urine composition. Additionally, oxalate and calcium are key dietary components to consider in kidney stone prevention strategies. Coffee has demonstrated diverse health benefits, including protection against cardiovascular disease, type 2 diabetes and neurodegenerative conditions. Its impact on blood pressure, glucose metabolism, and neuroprotection highlights its potential role in promoting overall well-being. Conclusions: Coffee consumption, particularly due to its caffeine content and other compounds like chlorogenic acid, may reduce the risk of kidney stone formation. Caffeine has shown anti-lithogenic properties, decreasing oxalate excretion and increasing magnesium and potassium excretion, potentially preventing stone formation. A study by P. Peerapen and V. Thongboonkerd highlighted caffeine's role in reducing crystal adhesion to renal cells as a key mechanism in preventing kidney stones. In summary, coffee's diverse components could provide protection against kidney stone development.